Pengaruh Model Numbered Heads Together Terhadap Hasil Belajar Tematik Terpadu Siswa Kelas V SD - Rahmayani, Dwi Putri; Suardiman, Farida (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2017)
This study aims to determine the effect of cooperative learning type numbered head together on integrated thematic learning outcomes in elementary school. The type of this research is quantitative research with the experimental method and the design of Quasi Exsperiment, with the form of Nonequivalent pretest-posttest control group design. The sample technique used is cluster random sampling with a sample consisting of two classes namely the experimental class and the control class. Analysis of the data of the two groups using the t test, obtained the results of tcount 3.302 and t table at a significant level of 0.05 at 2.010 so that tcount> t table. Thus it can be concluded that the Numbered Head Together type of cooperative learning model has a positive effect on integrated thematic material in class V SD.